2014
DOI: 10.1063/1.4893323
|View full text |Cite
|
Sign up to set email alerts
|

Resistance switching in epitaxial SrCoOx thin films

Abstract: Articles you may be interested inStrain effect caused by substrates on phase separation and transport properties in Pr0.7(Ca0.8Sr0.2)0.3MnO3 thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 32 publications
7
62
0
Order By: Relevance
“…Because the lattice constants of both BM-SCO and SRO are slightly larger than that of STO, the as-grown films were under relatively smaller compressive strain. All these results are quite consistent with our previous XRD results on BM-SCO 25 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Because the lattice constants of both BM-SCO and SRO are slightly larger than that of STO, the as-grown films were under relatively smaller compressive strain. All these results are quite consistent with our previous XRD results on BM-SCO 25 .…”
Section: Resultssupporting
confidence: 93%
“…Recently, we observed the bipolar RS behavior of brownmillerite SrCoO x (BM-SCO) thin film and found that the forming voltage ( V F ) could be lower than the set voltage ( V S ) 25 . This, along with diverse temperature-dependent resistivity behaviors in the LRS and HRS, led us to a new type of switching mechanism based on a local topotactic phase transformation of the SCO from a brownmillerite to perovskite structure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, brownmillerite SrCoO 2.5 (SCO) can undergo polymorphic phase transition under electric field control and has resistive switching behavior. 5,[7][8][9][10] Brownmillerite SrFeO x (SFO) with similar structure of SCO has been extensively studied due to its promising application in the fields of electrodes of fuel cell, magnetic storage, redox reaction catalyst, [11][12][13][14][15] etc. In addition, partial substitutions of the B specie of ABO 2.5 produce complex brownmillerite oxides such as Ca 2 FeAlO 5 , Ca 2 FeCoO 5 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Brownmillerite oxides such as SrFeO 2.5 (BM-SFO) are of particular interest due to their wide range of physical properties including thermoelectricity, fast oxygen-ion transport, catalysis, and topotactic phase transformation at low temperatures 15,16 . These properties allow BM oxides to be exploited for extensive applications such as in solid-oxide fuel cells, sensors, membranes for oxygen separation, photon catalysis, and memristors [17][18][19] . BM oxides have a perovskite-derived structure with parallel rows of ordered oxygen vacancies that create tetrahedral chains directed along [101] pc in every second (010) pc octahedral plane.…”
mentioning
confidence: 99%